DYNAMIC LIGHT SCATTERING BY NANO- AND MICRO-SIZED COMPLEXES IN THE SYSTEM K2ReBr6/p-AMINOBENZOIC ACID/HBr/H2O - Osmanova, S.N.; Kerimova, U.A.; Osmanov, N.S.; Ismailov, E.H.; Suleymanova, S.A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
K2ReBr6/p-aminobenzoic acid/HBr/H2O system using dynamic light scattering (DLS) and electronic absorption spectra (EAS) were studied. The formation of nano- and micro-sized complexes with hydrodynamic radius 0.001-2.8 Âµm within the temperature interval 293-333 KÂ andÂ as a function of concentration of hydrobromic acid and K2ReBr6/p-aminobenzoic acid ratio are shown.